2020
DOI: 10.1111/tmi.13511
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in the intensive care unit: alternative treatment regimens and association with mortality

Abstract: objectives Adequate anti-tuberculosis (TB) treatment is an important factor that can affect the patient's outcome. Higher mortality is found in patients who do not receive optimal treatment that includes isoniazid and rifampicin. The objective of this study is to evaluate the association of use of alternative TB treatment regimens (without rifampicin and isoniazid) and mortality among patients requiring intensive care. methods Retrospective cohort study, from January 2010 to December 2018. Patients aged > 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, there is inconsistent access to intravenous rifampicin and isoniazid in Hong Kong. Inability to give first-line treatment may be a contributing factor to excess mortality 23. Furthermore, our DAG-guided multivariable model showed that the RR of 1.68 (95% CI 1.18 to 2.40) was a direct estimation of the effect of second-line drugs on hospital mortality (table 3 and online supplemental figure 1).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, there is inconsistent access to intravenous rifampicin and isoniazid in Hong Kong. Inability to give first-line treatment may be a contributing factor to excess mortality 23. Furthermore, our DAG-guided multivariable model showed that the RR of 1.68 (95% CI 1.18 to 2.40) was a direct estimation of the effect of second-line drugs on hospital mortality (table 3 and online supplemental figure 1).…”
Section: Discussionmentioning
confidence: 82%
“…Most available ATTs are available in peroral formulations, making administration difficult in critically ill patients who often require endotracheal intubation and with multiorgan failure. Hypoalbuminaemia is one of the most common laboratory findings in TB patients in the intensive care unit and is an associated risk factor for a higher mortality[ 49 ]. Hypoalbuminaemia can contribute to gut oedema, impairing enteral absorption leading to low serum concentrations of ATTs, as well as impair the volume of distribution of ATTs by altering the drug binding of albumin-bound rifampicin and ethambutol[ 30 , 50 ].…”
Section: Treatment Of Tbmentioning
confidence: 99%
“…The characteristics of the critically ill patient, the route of administration, drug absorption, bio-availability, dose modification in case of hepatic and renal dys-function, and interaction with other drugs should be considered to ensure adequate plasma levels. Conventional regimens (rifampicin, isoniazid, pyrazinamide and oral ethambutol) have been shown to reduce mortality compared to alternative regimens (IV levofloxacin plus oral ethambutol plus IM streptomycin or IV amikacin, without rifampicin or isoniazid) [ 122 ]. Suboptimal concentrations of some drugs lead to recommend the intravenous use of specific treatments that are not always available in all countries.…”
Section: Is Tuberculosis a Concern In Intensive Care Units?mentioning
confidence: 99%